(untitled) (CIPEEX, 2026)
Aesthetics is becoming increasingly important, due to the rigid standards society imposes on individuals to feel included in universe. Faced with the various disharmonies that affect aesthetics, quality of life and daily life can also be altered. Diastemas are a frequent reason for dental office visits because they interfere with aesthetics. Composite resins, due to their versatility, can be used for a wide range of aesthetic solutions. The objective of this study is to report a clinical case of aesthetic resolution involving closure of an anterior-superior maxillary diastema and torsiversion of the upper central incisors, with the addition of composite resin using the direct technique. A female patient sought the UniEVANGÉLICA Dental Clinic with the main complaint of: "My upper teeth have spaces between them and are a little crooked. My lower teeth also have spaces, but I don’t mind because they are barely visible." The clinical examination revealed diastemas between the upper and lower central incisors, as well as a slight rotation of the upper central incisors. The proposed treatment plan was to close the upper diastema, which was bothering the patient, and to correct the position of the upper central incisors with the addition of composite resin, following the composite resin protocol. The use of direct-use composite resins provided immediate and satisfactory aesthetic results, achieving the desired success. Dental professionals must be up-to-date and knowledgeable about materials and techniques to achieve excellent results.